Modulation of visceral pain by brain nuclei and brain circuits and the role of acupuncture: a narrative review - Dou, Zhiqiang; Su, Na; Zhou, Ziyang; Mi, Aoyue; Xu, Luyao; Zhou, Jiazheng; Sun, Sizhe; Liu, Yanyi; Hao, Mingyao; Li, Zhaofeng (Frontiers in Neuroscience, 2023)
Visceral pain is a complex and heterogeneous pain condition that is often associated with painrelated negative emotional states, including anxiety and depression, and can exert serious effects on a patient's physical and mental health. According to modelling stimulation protocols, the current animal models of visceral pain mainly include the mechanical dilatation model, the ischemic model, and the inflammatory model. Acupuncture can exert analgesic effects by integrating and interacting input signals from acupuncture points and the sites of pain in the central nervous system. The brain nuclei involved in regulating visceral pain mainly include the nucleus of the solitary tract, parabrachial nucleus (PBN), locus coeruleus (LC), rostral ventromedial medulla (RVM), anterior cingulate cortex (ACC), paraventricular nucleus (PVN), and the amygdala. The neural circuits involved are PBN-amygdala, LC-RVM, amygdala-insula, ACC-amygdala, claustrum-ACC, bed nucleus of the stria terminalis-PVN and the PVN-ventral lateral septum circuit. Signals generated by acupuncture can modulate the central structures and interconnected neural circuits of multiple brain regions, including the medulla oblongata, cerebral cortex, thalamus, and hypothalamus. This analgesic process also involves the participation of various neurotransmitters and/or receptors, such as 5-hydroxytryptamine, glutamate, and enkephalin. In addition, acupuncture can regulate visceral pain by influencing functional connections between different brain regions and regulating glucose metabolism. However, there are still some limitations in the research efforts focusing on the specific brain mechanisms associated with the effects of acupuncture on the alleviation of visceral pain.Further animal experiments and clinical studies are now needed to improve our understanding of this area.